A Low-Cost Testbed for Neural Microelectrodes - Cat-Vu H. Bui; Neethu Maliakal; Hasan Ulusan; Andreas Hierlemann; Fernando Cardes (Proceedings)
The performances of microelectrode arrays for neural interfaces strongly depend on electrode design. Due to a lack of simulation tools, electrode engineers often have to refine new designs empirically. This process requires setups of electrical and electrophysiological hardware that are not specific to electrode testing and unnecessarily costly. We propose a low-cost testbed for specifically targeting metrics relevant to electrode performance and functions, which relies on an off-the-shelf measurement tool and only on components necessary for such testing. We experimentally demonstrate the platform by characterizing microelectrodes by means of impedance spectroscopy and recording the extracellular action potentials from in vitro primary rat neurons.